Biochemical identification and molecular characterization of Klebsiella pneumoniae isolated from street foods and drinks in Yogyakarta, Indonesia using 16S rRNA gene: - - Tri Yahya Budiarso; Charis Amarantini; Suhendra Pakpahan (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Budiarso TY, Amarantini C, Pakpahan S. 2021. Biochemical identification and molecular characterization of Klebsiella pneumoniae isolated from street foods and drinks in Yogyakarta, Indonesia using 16S rRNA gene. Biodiversitas 22: 5452-5458. Yogyakarta is best known as a student city in Indonesia. However, the fact that students spend almost full day in the school gave rise to the sale of a great variety of foods and drinks in its surrounding streets. Unfortunately, most street vendors do not pay attention to food hygiene. This study aims to identify the biochemical and molecular isolates of Klebsiella pneumoniae isolated from street foods and drinks in Yogyakarta using 16S rRNA gene. Data were collected from 120 samples of street foods and drinks sold at schools and several public places. The samples were enumerated using CCA medium to isolate suspected Klebsiella spp. colonies, then physiologically screened and identified using the API-20E kit. Positive isolates were isolated and amplified using the 16S rRNA gene marker for sequencing, which was then compared with the GenBank database to establish molecular identity. The results of biochemical identification obtained 11 isolates confirmed as K. pneumoniae and 1 isolate as K. oxytoca. The phylogenetic analysis showed that only 10 isolates were determined as K. pneumoniae with the reference sequences of K. pneumoniae from infected patients' respiratory and urinary tract. Furthermore, 2 isolates identified as Citrobacter sp. and Micrococcus sp., which are contaminated with Klebsiella spp. were highly found in street foods and drinks. Therefore, hygiene and sanitation need to be implemented when processing and serving these foods.